Effect of Catalyst-Assisted Hydrothermal/Organosolv Process for Fractionation of Parawood. Issue 1 (November 2020) - Srisuwansakda, Araya; Srinophakun, Penjit; Champreda, Verawat; Suriyachai, Nopparat
Abstract: Fractionation of lignocellulosic components is a pre-requisite in biorefineries in order to separate the main compositions of raw material for further maximum utilization to biofuels, chemicals, and materials. Generally, a single step process is often insufficient to assure full availability of polymeric sugars from raw material. Therefore, the purpose of this study is to investigate two-step fractionation comprising hydrothermal and organosolv processes for the efficient separation of lignocellulosic biomass with a promising recovered yield in terms of quality and quantity. In this study, the effects of acids and bases concentration were studied in the two-step fractionation process, since they play different important roles in separation process. It was observed that the optimal condition of hydrothermal process was performed at 180°C for 60 min in the presence of 3.3%(w/w) of H2SO4 followed by organosolv process at 200°C for 60 min with 5%(w/w) of NaOH, resulting in the efficiency of hemicellulose and lignin removal of 87.96% and 46.39%, respectively. In addition, the high recovery of hemicellulose as pentose sugars were observed. The remaining cellulose was obtained with 80.22%. These results demonstrated the successive hydrothermal and organosolv process for fractionation of Parawood.